A Christian ethical perspective on the moral status of the human embryo - J. M. Vorster (Acta Theologica)
This investigation focuses on the moral status of the human embryo from a Christian ethical perspective. The central theoretical argument is that the embryo has a particular standing before God and should therefore have a special standing in the eyes of human beings. The article examines three biblical concepts from the perspective of a biblical-theological hermeneutical model in order to unfold this argument. These are: the creation of the human being as a living being with the breath of God (nephesh); the creation of the human being in the image of God; and the biblical view of the human being as a covenantal being. The conclusion reached is that the human embryo must be regarded as a neighbour. Therefore, the commandment of neighbourly love, which is a core characteristic of deontological Christian ethics, should also be extended to include the human embryo.